Alternate PCR assays for screening of JH1 mutation associated with embryonic death in Jersey cattle. (February 2021) - Kumar, Anshuman; Gupta, Ishwar Dayal; Mohan, Govind; M. R., Vineeth; D., Ravi kumar; S., Jayakumar; Kataria, Ranjit Singh; Niranjan, Saket Kumar
Abstract: Jersey haplotype (JH) 1, a stop-gain lethal mutation in the CWC15 gene, causes embryonic losses in Jersey cattle. Two PCR based assays using Amplification Refractory Mutation System (T-ARMS-PCR) and restriction fragment length polymorphism (PCR-RFLP) were developed for screening of the JH1 in cattle. During the screening, seven among 30 Indian Jersey bulls were identified as carriers of the mutant JH1 allele, the first time in the country. These PCR assays are economical, rapid and accurate; and can be used separately or in combination for screening and cross-validation of the JH1 carriers in Jersey cattle. Highlights: Two PCR assays were developed for detection of Jersey haplotype-1 associated with embryonic death in Jersey cattle. These assays are rapid and economical for screening, and can be used for cross-validation of carriers. Screening of these haplotypes resulted in presence of carriers in Indian Jersey cattle with about 23% of frequencies.